The State of Antimicrobial Resistance Surveillance in the Military Health System: A Review of Improvements Made in the Last 10 Years and Remaining Surveillance Gaps. Issue 2 (1st February 2015) - Chandrasekera, Ruvani M.; Lesho, Emil P.; Chukwuma, Uzo; Cummings, James F.; Waterman, Paige E.
ABSTRACT: During a military public health laboratory symposium held in 1999, concerns were raised that the military health system lacked a standardized antimicrobial resistance (AMR) surveillance system that allowed comparison of data across sites, investigation of trends, and understanding of resistance mechanisms. The purpose of this review was to assess if current AMR activities in the military health system have addressed the aforementioned gaps. It was determined that much progress has already been made within the Department of Defense with respect to monitoring and understanding AMR through initiatives such as the Antimicrobial Resistance Monitoring and Research Program—a strong Department of Defense-wide surveillance program. These surveillance efforts can be made more robust through harmonization of testing and reporting structures across military treatment facilities, and by encouraging military treatment facility participation.